Technological ecosystems, transmedia, digital narratives and cyberradio - Chang Yánez, Beatriz; Vizuete Negrete, Washington; Vergara Torres, Consuelo; Barreth González, Alba (Scripta Mundi, 2022)
This study seeks to contribute to the debate about the influential transcendence of the technological, transmedia and narrative ecosystems for the establishment of new environments and formats for the conception, management and development of digital radio productions, supported by technological innovations that are turning radio Ecuadorian in a cybermedia. This research was based on the analysis of two variables: the systematic review of techniques for incorporating, using and applying radio digitalnarratives, arising from hypertext and transmedia convergence, expressive resources, interactive processes, establishing virtual production paths; and, to elucidate the media realization, of aesthetic use of technologies, tools and production formats, integration and virtual dimension, for contents adapted to the development of the multimedia and interactive nature for nodes and mobile links.The radio review and monitoring methodology was combined, quantitatively based on documentary analysis and application of the interpretive method, to qualitatively demonstrate that the technological change is the main generator of development opportunities in the digital industry, which I incorporate in computing in order to digitize the technical production processes. The results show an integrated strategy of multimedia techniques with the analog system in the phases of development and evolution of content productions, programmatic narrative. Verifying that the cyber radio is discovering its expressive possibilities, creating its own narratives, appropriate to the transformation of the communication ecosystem of the radio industry.
Keywords: digital narratives; multimedia narratives; digital stories and transmedia narrative; technological ecosystems